PEMANFAATAN TEKNOLOGI RFID MELALUI KARTU IDENTITAS UNTUK LINGKUNGAN KANTOR - Muhammad Reza (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2019)
As time goes on, technology become more advance. It makes everything simpler, thinner, and well organized. Even your money can be replaced by a single card. One of the latest system invented is Radio Frequency Identification or RFID. This system need media like smart chipped- card or nametag for emitting signal which then received by a tool called receiver / reader. In the office environment, RFID has a major role to create better supervision for empolyee and security. It can record attendance, give authorization to access, or even record bio data for manajement purpose. This RFID application in office is expected to make faster production and well-organized management.